2016
DOI: 10.1038/npp.2016.72
|View full text |Cite
|
Sign up to set email alerts
|

Phenome-Wide Association Study for Alcohol and Nicotine Risk Alleles in 26394 Women

Abstract: To identify novel traits associated with alleles known to predispose to alcohol and nicotine use, we conducted a phenome-wide association study (PheWAS) in a large multi-population cohort. We investigated 7688 African-Americans, 1133 Asian-Americans, 14 081 EuropeanAmericans, and 3492 Hispanic-Americans from the Women's Health Initiative, analyzing alleles at the CHRNA3-CHRNA5 locus, ADH1B, and ALDH2 with respect to phenotypic traits related to anthropometric characteristics, dietary habits, social status, psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…Therefore, PheWAS have the potential to deepen genomic knowledge regarding the range of phenotypic effects associated with GWAS-identified risk alleles. For example, a PheWAS of smoking and alcohol use in 26,394 women replicated prior asosciations between variants in ADH1B and alcohol use (e.g., alcohol servings per week, number of medium servings of wine per day, number of drinks of alcohol) as well as between variants in CHRNA3-CHRNA5 and smoking behaviors (e.g., cigarettes per day, age starte smoking cigarettes regularly; Polimanti, Kranzler & Gelernter, 2016). Further, the combination of PheWAS among affected individuals may also lead to an impoved understanding of SUD as well as other conditions.…”
Section: Limitations Of Sud Genetic Epidemiology Studiesmentioning
confidence: 83%
“…Therefore, PheWAS have the potential to deepen genomic knowledge regarding the range of phenotypic effects associated with GWAS-identified risk alleles. For example, a PheWAS of smoking and alcohol use in 26,394 women replicated prior asosciations between variants in ADH1B and alcohol use (e.g., alcohol servings per week, number of medium servings of wine per day, number of drinks of alcohol) as well as between variants in CHRNA3-CHRNA5 and smoking behaviors (e.g., cigarettes per day, age starte smoking cigarettes regularly; Polimanti, Kranzler & Gelernter, 2016). Further, the combination of PheWAS among affected individuals may also lead to an impoved understanding of SUD as well as other conditions.…”
Section: Limitations Of Sud Genetic Epidemiology Studiesmentioning
confidence: 83%
“…In addition to CHRNA5 - CHRNA3 - CHRNB4 loci, which is the international validated loci for smoking quantity and nicotine dependence, [3, 4, 5] the most widely studied gene in the dopaminergic pathway is the dopamine receptor D4, which is encoded by the DRD4 gene; among the most explored genetic variants are the variable number tandem repeat (VNTR), located in exon III of this gene, however, studies that evaluated single nucleotide polymorphisms (SNPs) are scarce [6, 7]. A few studies have explored the association of SNPs in the 5-hydroxytryptamine receptor 2A (HTR2A) gene with nicotine addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Although no large genomic investigation has been conducted on RSB, a recent genome-wide association study (GWAS) of age at first sexual intercourse indicated that the onset of sexual activity is genetically correlated to other reproductive and behavioral traits (Day et al, 2016). Our recent phenome-wide association study showed that risk alleles for alcohol-drinking behaviors are associated with reproductive health traits (Polimanti et al, 2016). These data suggest that alcohol use and abuse play a relevant role in RSB.…”
Section: Introductionmentioning
confidence: 99%